Frequency of Post Neonatal Tetanus Mortality in a Tertiary Care Center (Medical Forum Monthly, 2024)
Objective: To determine the frequency of post neonatal tetanus mortality in a tertiary care hospital.Study Design: Case series studyPlace and Duration of Study: This study was conducted at the Pediatric ward of Peoples medical college and hospital Nawabshah from January 2017 to December 2017.Materials and Methods: A total 98 children having clinical diagnosis of tetanus, who had lock jaw, stimulatory fits/spasm that has developed beyond 1 month of age were included in this study. The demographic and clinical data collected on a proforma was statistically analyzed and results were tabulated.Results: Frequency of post neonatal tetanus death was observed in 19.4% children. Rate of mortality was 21.7% in unvaccinated children as compare to 6.7% in vaccinated children (p=0.29).Conclusion: We conclude that tetanus remains a public health problem in our environment and that all stakeholders must work to achieve complete eradication of this disease by immunization. We recommend that vaccination during pregnancy and in infancy, as recommended in the National Program on Immunization (NPI). These recommendations could reduce the post-neonatal tetanus burden to its barest minimum and ultimately, the elimination of tetanus.